Great white [videorecording (DVD)] - Bowden, Katrina, 1988-; Jakubenko, Aaron, 1988-; Tsukakoshi, Kimie (RLJE Films, Shudder, 2021)
When a sea plane is destroyed in a freak accident, five people find themselves drifting on a raft. At the mercy of the tide and with no hope of rescue, the helpless situation takes a horrifying turn when they are terrorised by a ravenous great white.